Water Conservation Function of Artificial Forests in Kubuqi Desert - Han Qingchi; Wang Haichao; Sun Kai; Pei Zhiyong; Wang Han; Su Xiaoming; Yang Jianjun; Chen Hongwei (Shuitu baochi tongbao, 2023)
[Objective] Research was conducted on understory litter and soil hydrological function for artificial forests in the forest protection station in the eastern section of the Kubuqi Desert. The comprehensive weight value of various indicators of the artificial forests in this area were scientifically calculated, and the hydrological effect and water conservation function of artificial forest litter and soil were determined in order to provide theoretical guidance for the directional tending of returning sand to forest in this area and related sandy areas. [Methods] Five common types of artificial shelterbelts were used in the Ordos afforestation station in the Kubuqi Desert. The water-holding capacity of litter and soil were determined using field measurements and the indoor immersion method, and the water conservation function of each forest was assessed using a combination of the analytic hierarchy process (AHP) and the entropy-weight method (EWM). [Results] ① The litter thickness in each stand ranged from 6.56 to 22.20 mm, and the litter accumulation ranged from 1.44 to 13.62 t/hm2. Interception capacity for the different forest stands followed the order of Salix matsudana-Populus × euramericana mixed forest > Populus × euramericana forest > Pinus sylvestris forest >3-year S. matsudana forest >8-year S. matsudana forest. ② The maximum water-holding depth of litter was linearly related to the dry mass, and the maximum storage was about 1.36~2.04 L of precipitation in each stand. These results showed that the maximum water-holding capacity of the litter depended mainly on the dry weight of the litter, while related factors such as tree species, age, and meteorology indirectly affected the water-holding capacity by influencing the dry weight of the litter. ③ Logarithmic and power functions provided good representations of the dynamic water-holding capacity and dynamic water uptake of litter, respectively. ④ The saturated water-holding rate, capillary water-holding rate, and total porosity basically showed decreasing trends as soil depth increased, and soil bulk density showed an increasing trend. ⑤ The S. matsudana-Populus × euramericana mixed forest exhibited a higher water conservation function than the other forests, the Populus × euramericana and Pinus sylvestris forests had similar water conservation functions, and the S. matsudana forests had the lowest water conservation functions. [Conclusion] Construction of future artificial shelterbelts in desert regions should prioritize the cultivation of mixed forests, and a more scientific plan for the return of sand to forests should be developed by considering differences in the water conservation function between tree species.